The political future of social security in aging societies - Galasso, Vincenzo, 1967- (Cambridge, Mass. : MIT Press, 2006)
Doubts about the ability of industrialized countries to continue to provide a sufficient level of retirement benefits to a growing number of retirees has fueled much recent debate and inspired a variety of recommendations for reform. Few major reforms, however, have actually been implemented. In The Political Future of Social Security in Aging Societies, Vincenzo Galasso argues that the success of any reform proposals depends on political factors rather than economic theory. He offers a comparative analysis of the future political sustainability of social security in six countries with rapidly aging populations--France, Germany, Italy, Spain, the United Kingdom, and the United States. Using a quantitative approach, he finds that an aging population has political as well as economic effects: an older electorate will put pressure on politicians and policy-makers to maintain or even increase benefits. Galasso evaluates how each country's different political constraints shape its social security system, considering such country-specific factors as the proportion of retirees in the population, the redistributive feature of each system, and the existing retirement policy in each country. He concludes that an aging population will lead to more pension spending; yet postponing retirement mitigates the impact of this, and may be the only politically viable alternative for social security reform.
Crucial features of the social security debate: a cross-country analysis -- Theories of welfare state expansion and retrenchment -- Assessing the political sustainability of social security systems: a theoretical framework -- The future of the social security system in France -- The future of the social security system in Germany -- Political sustainability and reforms in Italy -- Political sustainability and the silent reform in Spain -- Political sustainability in a redistributive system: the United Kingdom -- Political sustainability in a redistributive system: The United States -- Demographics, political sustainability, and reform options: a cross-country comparison.
Includes bibliographical references (pages 235-243) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Social security -- Case studies; Social security -- Forecasting; Sécurité sociale -- Études de cas; Sécurité sociale -- Prévision.; POLITICAL SCIENCE -- Public Policy -- Social Security; Social security; Social security -- Forecasting; Sociale zekerheid; Veroudering (demografie); ECONOMICS/Political Economy; SOCIAL SCIENCES/Political Science/Public Policy & Law; Case studies; Case studies; Études de cas